Mycobacterium tuberculosis protein kinase G acts as an unusual ubiquitinating enzyme to impair host immunity. (2nd May 2021) - Wang, Jing; Ge, Pupu; Lei, Zehui; Lu, Zhe; Qiang, Lihua; Chai, Qiyao; Zhang, Yong; Zhao, Dongdong; Li, Bingxi; Su, Jiaqi; Peng, Ruchao; Pang, Yu; et al.
Abstract: Upon Mycobacterium tuberculosis (Mtb) infection, protein kinase G (PknG), a eukaryotic‐type serine‐threonine protein kinase (STPK), is secreted into host macrophages to promote intracellular survival of the pathogen. However, the mechanisms underlying this PknG–host interaction remain unclear. Here, we demonstrate that PknG serves both as a ubiquitin‐activating enzyme (E1) and a ubiquitin ligase (E3) to trigger the ubiquitination and degradation of tumor necrosis factor receptor‐associated factor 2 (TRAF2) and TGF‐β‐activated kinase 1 (TAK1), thereby inhibiting the activation of NF‐κB signaling and host innate responses. PknG promotes the attachment of ubiquitin (Ub) to the ubiquitin‐conjugating enzyme (E2) UbcH7 via an isopeptide bond (UbcH7 K82‐Ub), rather than the usual C86‐Ub thiol‐ester bond. PknG induces the discharge of Ub from UbcH7 by acting as an isopeptidase, before attaching Ub to its substrates. These results demonstrate that PknG acts as an unusual ubiquitinating enzyme to remove key components of the innate immunity system, thus providing a potential target for tuberculosis treatment. SYNOPSIS: The Mycobaterium tuberculosis effector protein PknG acts as an unusual ubiquitinating enzyme to promote the polyubiquitination and degradation of its substrates TRAF2 and TAK1 via a two‐step cascade, thereby suppressing host innate immune responses. PknG acts as an unconventional E1 enzyme to catalyze covalent ubiquitin conjugation to UbcH7. PknG functions as an isopeptidase to release ubiquitin from the E2 enzyme UbcH7. PknG promotes substrate polyubiquitination depending on its E3 ligase activity. Abstract : The Mycobaterium tuberculosis effector protein PknG acts as an unusual ubiquitinating enzyme to promote the polyubiquitination and degradation of its substrates TRAF2 and TAK1 via a two‐step cascade, thereby suppressing host innate immune responses.